Pengaruh Kualitas Informasi, Kualitas Sistem Informasi, dan Perceived Usefulness terhadap Kepuasan Pengguna Sistem Aplikasi Keuangan Tingkat Instansi Modul Penganggaran pada Satuan-Satuan Kerja Lingkup Pembayaran KPPN Madiun - Agustina Rahayuningtyas (Jurnal Manajemen dan Inovasi (MANOVA), 2022)
Sistem Aplikasi Keuangan Tingkat Instansi (SAKTI) Modul Penganggaran has been applied to all working units of Kantor Pelayanan Perbendaharaan Negara Madiun (KPPN) working area since 2020. After two years of implementation, it is necessary to evaluate SAKTI Modul Penganggaran users’ satisfaction as one of the indicators of the success of SAKTI Modul Penganggaran. This study aims to determine the impact of information system quality, information quality, and perceived usefulness on SAKTI Modul Penganggaran users’ satisfaction in the KPPN Madiun working area. The approach used in this study is a quantitative method. The results showed that the information system quality, information quality, and perceived usefulness simultaneously or partially had a positive and significant impact on the SAKTI Modul Penganggaran users’ satisfaction.